Psychotic disorders and repeat offending: systematic review and meta-analysis. - Fazel, S; Yu, R (2011)
OBJECTIVE: To undertake a systematic review and meta-analysis on the risk of repeat offending in individuals with psychosis and to assess the effect of potential moderating characteristics on risk estimates. METHODS: A systematic search was conducted in 6 bibliographic databases from January 1966 to January 2009, supplemented with correspondence with authors. Studies that reported risks of repeat offending in individuals with psychotic disorders (n = 3511) compared with individuals with other psychiatric disorders (n = 5446) and healthy individuals (n = 71 552) were included. Risks of repeat offending were calculated using fixed- and random-effects models to calculate pooled odds ratios (ORs). Subgroup and meta-regression analyses were conducted to examine how risk estimates were affected by various study characteristics including mean sample age, study location, sample size, study period, outcome measure, duration of follow-up, and diagnostic criteria. RESULTS: Twenty-seven studies, which included 3511 individuals with psychosis, were identified. Compared with individuals without any psychiatric disorders, there was a significantly increased risk of repeat offending in individuals with psychosis (pooled OR = 1.6, 95% confidence interval [CI] = 1.4-1.8), although this was only based on 4 studies. In contrast, there was no association when individuals with other psychiatric disorders were used as the comparison group (pooled OR = 1.0, 95% CI = 0.7-1.3), although there was substantial heterogeneity. Higher risk estimates were found in female-only samples with psychosis and in studies conducted in the United States. CONCLUSIONS: The association between psychosis and repeat offending differed depending on the comparison group. Despite this, we found no support for the findings of previous reviews that psychosis is associated with a lower risk of repeat offending.